Strategic Mobility: An Expanded View with Focus on Readiness and Sustainability - Baskett, Roger D. (1991)
Strategic mobility is a phrase often used in today's military jargon. In fact, strategic mobility is an integral part of the military strategy supporting the national security interests of the United States. When most military personnel think of strategic mobility, they usually define the concept in terms of air lift and sealift capability. The Secretary of Defense in his 1990 Joint Military Net Assessment to the U.S. Congress refers to strategic mobility as a strategic lift triad of airlift, sealift, and prepositioning. Certainly these three aspects of strategic mobility are crucial to a viable force projection capability. This paper focuses on what I believe are the two key concepts that most accurately describe strategic mobility--readiness and sustainability. Two cases studies are developed to serve as points of reference in explaining how readiness and sustainability combine to form strategic mobility. The first case study describes how the United Kingdom projected a military force to the South Atlantic in response to the Falkland Islands' crisis in 1982. The second case study depicts the United States' military deployment to Saudi Arabia following the Iraqi invasion of Kuwait in August 1990. Following the case studies, an analysis of strategic mobility is presented.